Bioelectricity Generation of Coconut Waste -based Double Chamber Microbial Fuel Cell with Various Substrate Compositions - Siti Kudnie, Sahari; Nasley Ursula Mundi, Ujai; Sabhah, Mohd Rafe; Martin, Anyi; Kuryati, Kipli; Zainab, Ngaini; Yanuar Zulardiansyah, Arief; Muhammad Rusop, Mahmood; Abdul Rahman, Kram; Marini, Sawawi; Asmahani, Awang; Kasumawati, Lias; et al. (UNIMAP, 2022)
The aim of this study was to investigate the generation of electricity in a microbial fuel cell (MFC) using coconut waste as substrate with various compositions. Different types of substrate with different pH values were tested in dual-chamber MFC. The maximum voltage level reached 699mV under alkaline condition after day 7th, which was considerably higher than those previously reported in literature using solid waste substrates. The series connection of the coconut waste MFC with boost converter module showed the ability to light up the bulb. Our results showed that implementation of local organic waste was promising in fabricating MFC for home appliances.